A Multilevel Approach to Scale Development in Sport Tourist Nostalgia. (November 2017) - Cho, Heetae; Lee, Hyun-Woo; Moore, DeWayne; Norman, William C.; Ramshaw, Gregory
Nostalgia has been identified as an essential factor to understand sport tourists' behavioral intentions. However, a measurement model to examine nostalgia has not been developed in the field of sport tourism. The purpose of this study was to develop a valid and reliable Nostalgia Scale for Sport Tourism (NSST) to measure sport tourists' nostalgia. A multilevel analysis was used in order to avoid biases caused by common characteristics within a travel group. The scale conceptualized sport nostalgia as a five-dimensional construct reflecting sport tourists' nostalgia of sport team, environment, socialization, personal identity, and group identity and showed adequate psychometric properties in assessing sport-specific nostalgia. The NSST scale developed here can be a useful tool for future empirical studies aiming to better understand sport spectator nostalgia and identify the role of nostalgia in sport tourism.